OPTIONS FOR REGISTRATION AND ANALYSIS OF WANTED VIBROACOUSTIC SIGNAL IN LABVIEW SOFTWARE PRODUCT - Sergei Olegovich Gaponenko (Вестник Северо-Кавказского федерального университета, 2022)
The currently available software designed for recording and processing vibroacoustic signals do not always allow meeting the entire range of the requirements for work with wanted signals. The software packages in question include LabVIEW, Measurement Studio, LabWindows/CVI, Agilent VEE, while LabVIEW has proven the most convenient in terms of building a virtual device for registering, processing, and comparing vibroacoustic signals.